Influence of Internal Flow on the Performance of High-Speed Centrifugal Pumps with a Fully Sealed Structure - Xinyi Lin; Beile Zhang; Ming Zhang; Yongli Zhao; Tianwei Lai; Liang Chen; Rong Xue (Applied Sciences, 2022)
A high-speed centrifugal pump with a fully sealed structure has the advantages of a small size, no external leakage, and being pollution-free. The inner leakage passage of a pump with a fully sealed structure includes the tip clearance and the hub clearance. The hub clearance, the lubrication passage of the bearing, and the clearance between the stator and the rotor of the built-in motor constitute the internal flow channel. As a consequence of hub leakage, the complexity of the flow field increases and performance of the pump is affected. However, hub leakage also lubricates the bearing and cools the motor by flowing through the internal flow channel. To obtain the actual flow field distribution and external characteristics of the pump, a coupling calculation based on a conventional CFX simulation and MATLAB was carried out. The results show that hub leakage promotes an increase in tip leakage and changes the distribution of the main flow field. Moreover, hub leakage also significantly affects the efficiency of the pump. Compared with hub leakage, the internal flow has a greater impact on the performance of the pump. The numerical simulation results of the internal flow model are similar to the experimental results, with the maximum absolute error of the head at 0.3 m and the maximum absolute error of the efficiency at 1.7%, indicating that the internal flow model is effective at predicting the performance of the high-speed centrifugal pump with a fully sealed structure.